Soil management practices: chemical and spectroscopic characterization - Nogueira, Barbara Arruda; Merlin, Nathalie; Santos, Poliana Macedo dos; Santos, José Alfredo Baptista dos; Saab, Sergio da Costa; Tonial, Larissa Macedo dos Santos (Scientia Agraria Paranaensis, 2018)
The aim of this study was to evaluate the possibility to apply chemical and spectroscopic analysis, coupled with chemometric tools, as a rapid method for soil characterization. Soil samples from different depths (0-10, 10-20 and 20-30 cm) and sites (fallow area for 5 years, area of no-tillage for 10 years and native forest) were applied in this study. Soil chemical characterization based on the concentration of macronutrients (P, K Ca, and Mg), micronutrients (Mn, Fe, Zn, and Cu), the level of aluminum, pH, organic matter (OM) and humification degree. For spectroscopic characterization, only the humic acid (HA) fraction was analyzed in the mid infrared spectrometer. Principal Components Analysis (PCA) and Hierarchical Clustering Analysis (HCA) showed clusters based on the management systems. These results support the application of chemometric toolls to evaluate the quality of soil providing a simple and rapid method for the soil science.